Efficacy of The Immunotargeting Therapeutic Antibody Trastuzumab in HER2-Positive Advanced Gastric Cancer: A Meta-Analysis - Yunxiao, Yang; Bihua, Lin; Huahui, Li; Yanfang, Liang; Ziyu, Ye; Yang, Ma; Long, Feng; Mingyuan, Huang; Keyuan, Zhou; Jincheng, Zeng (International Journal of Inflammation Research, 2018)
Gastric cancer is one of the most common types of cancer in the world, usually diagnosed at an advanced stage. Despite the advances in specific anticancer agents' development, the survival rates remain modest, even in early stages. HER2 overexpression was identified on 15% - 20% of gastric cancer patients. Trastuzumab-based chemotherapy provides obvious efficacy improving outcomes of HER2 positive gastric cancer patients. We performed a meta-analysis to estimate the efficacy of the addition of trastuzumab over chemotherapy. We identified randomized controlled trials (RCTs) which compare the addition of trastuzumab therapy to chemotherapy alone reporting progression-free survival (PFS), time to progression (TTP), overall survival (OS), and/or response rates as our eligible trials. Night trials including 1101 patients were eligible for analysis. Trastuzumab therapeutic partners were cisplatin (9 RCTs), 5-fluorouracil (8 RCTs), capecitabine (6 RCTs), irinotecan (1 RCTs), docetaxel (1 RCTs), oxaliplatin (1 RCTs), and leucovorin (1 RCTs). The addition of trastuzumab agents improved OS (HR = 0.80; 95% CI = 0.72 - 0.89), PFS (HR = 0.70; 95% CI = 0.59 - 0.83), TTP (HR = 0.69; 95% CI = 0.57 - 0.83), and overall response rate (RR = 1.22; 95% CI = 0.94 - 1.59), DCR (RR = 1.19; 95% CI = 1.10 - 1.28). Our meta-analysis affirmed the efficacy of adding trastuzumab agent to chemotherapy in HER2 positive gastric cancer.
Keywords: trastuzumab; gastric cancer; human epidermal growth factor receptor 2; meta-analysis